Seed priming with salicylic acid enhances salt stress tolerance by boosting antioxidant defense in Phaseolus vulgaris genotypes - Mohammad Reza Karimi; Manijeh Sabokdast; Hamid Korang Beheshti; Ali Reza Abbasi; Mohammad Reza Bihamta (BMC Plant Biology)
Abstract Salinity stress significantly threatens seed germination, plant growth, and agricultural productivity, necessitating effective mitigation strategies. This study evaluates the potential of salicylic acid (SA) pretreatment to alleviate the detrimental effects of salinity on common bean (Phaseolus vulgaris) genotypes. SA, a phenolic plant hormone, is crucial for regulating growth, stress responses, and essential physiological processes, including seed germination and ion transport. Previous research has established the general benefits of SA in enhancing stress tolerance, but the specific mechanisms and effects on common bean genotypes remain underexplored. This research focuses on the impact of salinity on the germination and seedling growth of various common bean genotypes, the efficacy of SA pretreatment in enhancing these genotypes' tolerance to salinity stress, and the underlying physiological and biochemical mechanisms, particularly involving the antioxidant defense system. The research was conducted in two phases: germination and seedling growth. Ten genotypes and two commercial varieties were exposed to varying salinity levels alongside SA concentrations to assess germination performance. Subsequently, six genotypes and one variety were evaluated for seedling growth under controlled and salt stress conditions (100 mM and 200 mM NaCl), with SA treatments at 0, 0.5, and 1 mM. Results revealed that salinity severely impaired germination traits, which were significantly enhanced by SA pretreatment. During the seedling growth phase, salinity stress resulted in reduced protein, chlorophyll, and carotenoid content, decreased potassium (K⁺) levels, and diminished water content, while increasing electrolyte leakage, malondialdehyde (MDA) levels, sodium (Na⁺) concentrations, enzyme activities, and proline levels. Importantly, SA pretreatment elevated chlorophyll and protein concentrations, improved water retention, and moderated K⁺ and Na⁺ levels, including their ratios under stress conditions. SA pretreatment also significantly enhanced the antioxidant defense system, reducing oxidative damage induced by salinity stress. Principal component analysis (PCA) successfully categorized the genotypes into semi-tolerant, tolerant, semi-sensitive, and sensitive classes based on their stress responses. Notably, the Jules variety exhibited exceptional resilience during both germination and seedling growth stages, indicating its potential as a superior candidate for cultivation in salt-affected regions. This study highlights SA pretreatment as an effective strategy to enhance salinity stress resilience in common bean genotypes. The novelty of this work lies in the detailed elucidation of SA's role in modulating antioxidant defenses and ion homeostasis in different genotypes, providing new insights into breeding programs and agricultural practices aimed at improving crop resilience and productivity in increasingly saline environments.